2014
DOI: 10.1007/s10072-014-1847-9
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular evoked myogenic potentials in Bell’s palsy

Abstract: The aim of the present study was to evaluate vestibular nerve involvement in patients with Bell's palsy with ocular and cervical vestibular evoked myogenic potentials (oVEMP and cVEMP). Ten patients who were diagnosed with Bell's palsy and ten healthy controls were included. All patients underwent VEMP recordings within six days after their initial presentation. Patients with Bell's palsy had greater oVEMP asymmetry ratio comparing to healthy controls (-38,4±28,7% vs -1,3±19.3%, p=0.005). As well N10 latencies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 10 publications
1
0
0
Order By: Relevance
“…Based on our finding, the question is raised about the clinical significance of the cVEMP response in APFP. Consistent with our finding, a previous study also reported that the cVEMP asymmetry ratio was not different between patients with BP and normal controls [ 25 ].…”
Section: Discussionsupporting
confidence: 93%
“…Based on our finding, the question is raised about the clinical significance of the cVEMP response in APFP. Consistent with our finding, a previous study also reported that the cVEMP asymmetry ratio was not different between patients with BP and normal controls [ 25 ].…”
Section: Discussionsupporting
confidence: 93%